Analgesic diterpenoids with diverse carbon skeletons from the leaves of Rhododendron auriculatum. (December 2019) - Sun, Na; Feng, Yuanyuan; Zhang, Qihua; Liu, Junjun; Zhou, Haofeng; Zhang, Hanqi; Zheng, Guijuan; Zhou, Junfei; Yao, Guangmin
Abstract: Sixteen diterpenoids including nine undescribed ones, named rhodoauriculatols A−I, were isolated from the leaves of Rhododendron auriculatum Hemsl. Sixteen diterpenoids belong to seven diverse carbon skeletons, which were classified into 1, 10- seco -grayanane, 1, 10:2, 3-di seco -grayanane, A- homo -B- nor - ent -kaurane, ent -kaurane, 4, 5- seco - ent -kaurane, leucothane, and grayanane, respectively. Their structures were determined by the detailed HRESIMS, 1D and 2D NMR, UV, and IR data analysis, and their absolute configurations were established by single crystal X-ray diffraction analysis, electronic circular dichroism (ECD) data analysis, ECD calculation, as well as chemical methods. Rhodoauriculatols A−C possess a rare 1, 10- seco -grayanane diterpene skeleton. Rhodoauriculatol D is the second example of the 1, 10:2, 3-di seco -grayanane diterpenoids, and rhodoauriculatol E is the fourth example of the A- homo -B- nor - ent -kaurane diterpenoids. Rhodomicranone E was reported as a natural product for the first time. All the isolated sixteen diterpenoids showed analgesic activities in the acetic acid-induced writhing test. Rhodoauriculatols B, E−G, rhodomicranone E, pierisformoside F, and micranthanoside A showed significant analgesic activities with the inhibition rates over 40%, and their preliminary structures-activity relationships were studied. Graphical abstract: Sixteen diterpenoids with seven carbon skeletons classified into 1, 10- seco -grayanane, 1, 10:2, 3- diseco -grayanane, pierisketone, ent -kaurane, 4, 5- seco - ent -kaurane, leucothane, and grayanane were isolated from the leaves of Rhododendron auriculatum . Rhodoauriculatols B, E−G, rhodomicranone E, pierisformoside F, and micranthanoside A showed significant analgesic activities with the inhibition percent in excess of 40%. Image 1 Highlights: Sixteen diterpenoids with seven diverse carbon skeletons were isolated. Rhodoauriculatols A−C possess a rare 1, 10- seco -grayanane diterpene skeleton. Rhodoauriculatol D is the second example of 1, 10:2, 3- diseco -grayanane diterpenoids. Rhodomicranone E was isolated as a natural product for the first time. Some diterpenoids showed significant analgesic activities.